Distribution and abundance of muskoxen (Ovibos moschatus) and Peary caribou (Rangifer tarandus pearyi) on Graham, Buckingham, and southern Ellesmere islands, March 2015 - Anderson, Morgan; Kingsley, Michael C.S. (Rangifer, 2017)
We flew a survey of southern Ellesmere Island, Graham Island, and Buckingham Island in March 2015 to obtain estimates of abundance for muskoxen and Peary caribou. Generally, muskoxen were abundant north of the Sydkap Ice Cap along Baumann Fiord, north of Goose Fiord, west and north of Muskox Fiord, and on the coastal plains and river valleys east of Vendom Fiord. Although few, they were also present on Bjorne Peninsula and the south coast between the Sydkap Ice Cap and Jakeman Glacier. We observed a total of 1146 muskoxen. Calves (approximately 10-months old) made up 22% of the observed animals. The population estimate was 3200 ± 602 SE (standard error) muskoxen, the highest muskox population size ever estimated for southern Ellesmere, Graham and Buckingham islands. This could be because previous efforts typically surveyed only a portion of our area or focused elsewhere, or the results were provided only as minimum counts rather than estimates of abundance. Regardless, our results indicate that the muskox population has recovered from low levels in 2005 of 312-670 (95% confidence interval [CI]) individuals. Peary caribou abundance appears to be low. We only saw 38 Peary caribou during our 2015 survey. This confounds appraisal of possible abundance change since 2005, when 109-442 caribou (95% CI) were estimated to inhabit the same surveyed area. We estimated 183 ± 128 SE Peary caribou, and suggest that their numbers are likely stable at low density on southern Ellesmere Island.